Seasonal patterns in Arctic planktonic metabolism (Fram Strait - Svalbard region) - Vaquer-Sunyer, Raquel; Duarte, Carlos M.; Regaudie-de-Gioux, A; Holding, Johnna; García-Corral, LS; Reigstad, Marit; Wassmann, Paul (Biogeosciences, 2013)
The metabolism of the Arctic Ocean is marked by extremely pronounced seasonality and spatial heterogeneity associated with light conditions, ice cover, water masses and nutrient availability. Here we report the marine planktonic metabolic rates (net community production, gross primary production and community respiration) along three different seasons of the year, for a total of eight cruises along the western sector of the European Arctic (Fram Strait – Svalbard region) in the Arctic Ocean margin: one at the end of 2006 (fall/winter), two in 2007 (early spring and summer), two in 2008 (early spring and summer), one in 2009 (late spring–early summer), one in 2010 (spring) and one in 2011 (spring). The results show that the metabolism of the western sector of the European Arctic varies throughout the year, depending mostly on the stage of bloom and water temperature. Here we report metabolic rates for the different periods, including the spring bloom, summer and the dark period, increasing considerably the empirical basis of metabolic rates in the Arctic Ocean, and especially in the European Arctic corridor. Additionally, a rough annual metabolic estimate for this area of the Arctic Ocean was calculated, resulting in a net community production of 108 g Cm−2 yr−1.